THE USE OF CALCIUM IN QUAILS DURING EGG HATCHING PHASE BY ADDING YACON LEAF POWDER (Smallanthus sonchifolius) - Emerson Umbu Hemur Patangara; Vitus Dwi Yunianto; Bambang Sukamto; Lilik Krismiyanto (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
The goal of this research is to find out the use of calcium in quails during egg hatching phase by adding yacon leaf powder (Smallanthus sonchifolius). The subject used were 160 quail birds that are in the phase of hatching eggs at the age of 5 weeks, weighing 135,81 ± 3,25 gr. The method of this research was Completely Randomized Design (CRD) with 5 treatments and 4 replication, every tested units consist of 8 birds. The treatment applied consist of T0 = basal ration, T1 = basal ration+ 1% yacon leaf powder, T2 = basal ration+ 2% yacon leaf powder, T3 = basal ration+ 3% yacon leaf powder and T4 = basal ration + 4% yacon leaf powder. The parameter being measured includes the consumption of calcium, calcium's retention, weight of the shell, thickness of the shell and the production of the eggs. The data was analyzed by using Analysis of Variants (ANOVA) with a significance level of 5% and if significantly affected it will continue with Duncan's Multiple Distance Test. The result shows that the significant effect of adding yacon leaf powder (P<0.05) on calcium’s retention and the production of the eggs, but it did not affect (P>0.05) on the consumption of calcium, the weight of the shell and the thickness of the shell. In summary, by adding the yacon leaf powder until level 4% in ration, it may increase the use of egg calcium in quailduring egg hatching phase.